Bakar Batu culture as a reflection of Pancasila ideology at early childhood education - KARYADI, A.C; KHASANAH, U. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research is intended to explore and discover values contained in Bakar Batu Culture, as implementation and reflection of the Pancasila ideology that is inserted in learning at the level of early childhood education. Through a qualitative descriptive approach with a phenomenological approach. The findings in the field of this study illustrate that the values contained in Bakar Batu culture are in accordance with the values contained in the Pancasila ideology to foster a sense of nationalism and patriotism towards children from an early age.RESUMEN El objetivo de esta investigación es explorar y descubrir los valores contenidos en la cultura Bakar Batu, como una implementación y reflejo de la ideología de Pancasila que se inserta en el aprendizaje a nivel de la educación de la primera infancia. A través de un enfoque descriptivo cualitativo con un enfoque fenomenológico. Los hallazgos en el campo de este estudio ilustran que los valores contenidos en la cultura Bakar Batu están de acuerdo con los valores contenidos en la ideología de Pancasila para fomentar un sentido de nacionalismo y patriotismo hacia los niños desde una edad temprana.